T-backs, t-shirts, COAT, and suit - Konigsburg, E. L. (Aladdin Paperbacks, 2008)
Spending the summer in Florida with her stepfather's sister who operates a "meals-on-wheels" van, twelve-year-old Chloe and her aunt become involved in a controversy surrounding the wearing of T-back bathing suits.